Biotransformation of bioactive compounds in seaweed through fermentation with marine endophytic fungi as antioxidant - Nur Haliza Ghea; Dyah Hardiningtyas Safrina; Tarman Kustiariyah (BIO Web of Conferences)
Sargassum polycystum is a brown seaweed with potential antioxidant properties due to its bioactive components. These bioactive components can be altered through biotransformation by fermentation. This fermentation can be carried out using marine endophytic fungi. The purpose of this study is to determine effect of fermentation process using the marine endophytic fungi Trichoderma harzianum KTR3 and KTR4 on the bioactive components and antioxidant activity. Sargassum polycystum and fermented Sargassum polycstum will be macerated using ethyl acetate solvent for 72 hours. Sargassum polycstum extract and Sargassum polycstum fermented with KTR3 and KTR4 showed the presence of tannins, saponins, steroids, and terpenoids. Fermentation treatment with Trichoderma harzianum KTR3 resulted a non-significant increase in antioxidant activity, indicated by a decrease in IC50 values in the fermented Sargassum polycstum extract. Metabolite profiling revealed an increase in the composition of compounds in Sargassum polycstum fermented with the KTR3 isolate, identifying 52 compounds, of which 36 were new biotransformation products. Marker compounds in fermented Sargassum polycstum extract are citrinin and pheophorbide A.